The International Association for Military Geosciences: A History to 2017 - Rose, Edward P. F. (Scientia Militaria - South African Journal of Military Studies, 2018)
The International Association for Military Geosciences (IAMG) was founded in 2013 at Aviemore in Scotland, during the 10th International Conference on Military Geosciences. The conference series had begun in 1994 in the United States, with subsequent almost biennial meetings alternating between Europe and North America. Initially, geological in their focus, however, the meeting themes broadened over the years to embrace military aspects of both geology and geography, and subsequently geosciences as a whole. Numbering was introduced (and applied retrospectively) in 2005, and the series title stabilised in 2009. The IAMG foundation reflected a developing international interest in military geosciences, evidenced by a significant number of books and journal articles as well as ancillary conferences focused on this discipline in recent years.